The impact of high-rise residential towers on urban structure - Faris Hussain, Rusul; Falah Mahdi Hadi, Falah (Journal of Planner and Development, 2025)
High-rise residential towers are of interest to investors in modern trends of architectural projects, as they are characterized by their ability to provide residential spaces in cities, especially those characterized by high population densities compared to the area, as high-rise towers combine modern architectural investment trends and planning challenges facing the city. In light of the planning challenges, high-rise residential towers face several challenges as a result of the high population densities in them, the most prominent of which are environmental challenges, as the towers affect the environment and the infrastructure, especially transportation, as interest in developing the infrastructure, especially transportation, is an important and simultaneous axis with planning for residential towers, as it is necessary to provide a transportation network that provides ease of movement and reduces the pressure of residents on the infrastructure in a manner that is consistent with their daily movement to reach workplaces and events. On the other hand, high-rise residential towers require in their planning to find a balanced rhythm between the urban structure and the identity of the place. High-rise residential towers provide investment opportunities if they are carried out according to a well-thought-out urban plan, taking into account the planning challenges associated with the infrastructure and the environment in a manner that ensures the quality of life for residents.  In this research, the spotlight was shed on the most prominent international experiences as inspiring models, combining architectural innovation and urban planning for the purpose of achieving the goals of residential towers to benefit from the exploitation of the least area in light of taking into account planning challenges.